2018
DOI: 10.1016/j.cjtee.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Phantom limb pain: A literature review

Abstract: Since the phantom limb sensation was first described by the French military surgeon Ambroise Pare in the 16th century, the number of studies surrounding phantom limb pain has increased every year. Especially in recent decades, scientists have achieved a better understanding of the mechanism and treatment of phantom limb pain. Although many hypotheses have been agreed and many treatments have been proven effective, scientists still do not have a very systematic understanding of the phantom limbs. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 28 publications
1
50
0
18
Order By: Relevance
“…Despite comparable experience, physiatrists estimated a significantly higher prevalence of both PN and PLP ( P < 0.05). Given that PN can be a late-developing phenomenon, 6 , 29 this discrepancy in estimated prevalence may be explained by a longer follow-up duration among physiatrists. 30 However, our study found no significant association between duration of follow-up and exposure to PN/PLP.…”
Section: Discussionmentioning
confidence: 99%
“…Despite comparable experience, physiatrists estimated a significantly higher prevalence of both PN and PLP ( P < 0.05). Given that PN can be a late-developing phenomenon, 6 , 29 this discrepancy in estimated prevalence may be explained by a longer follow-up duration among physiatrists. 30 However, our study found no significant association between duration of follow-up and exposure to PN/PLP.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding adjunctive therapy, it includes mirror therapy (MT), transcutaneous nerve stimulation, electroconvulsive therapy, biofeedback, acupuncture, massage, and so on [19]. MT was first reported in 1996, which helped to reduce PLP by eliminating the separation of visual proprioception in the brain [20].…”
Section: Treatment Of Plpmentioning
confidence: 99%
“…8 An example Carel (2011) draws from Merleau-Ponty is the phenomenon of phantom limbs. Phantom limbs are still considered a mysterious phenomenon in science (Kaur and Guan, 2018). How is it that we can have sensory experiences from a limb that has been amputated?…”
Section: 3mentioning
confidence: 99%